Estilos de liderazgo de los directivos docentes y su relación con el modelo de gestión educativa (2019)
The objective to follow was to analyze the relationship between leadership styles and management models in a Barranquilla Institution. The paradigm is positivist, the approach is quantitative and according to the control of the variables is non-experimental type and according to the study objective is to correlate in view that its objective is to identify probable relationships between variables; the research design is cross-sectional, field-based, a case study; the sample is census, the techniques to be used are the surveys; Two instruments will be used that will measure the leadership styles and management model of the teaching managers. The research was conducted in the city of Barranquilla, with the target population being teachers, educational directors, coordinators, and psychologists of the Concentra Cevillar District Educational Institution. This study allows directing the institutions to improve the process and the educational quality in the institution. In the result, it is evidenced according to the correlation coefficient product moment of Pearson that there is a direct and significant relationship between the educational quality management model and the leadership style, thus confirming the hypothesis proposed in this study.